Manual practico para operadores forestales (INRENA, CIFOR, FONDEBOSQUE, 2004)
The purpose of this manual is to serve as a support and reference tool to be used in the training of timber operators on reduced impact harvesting techniques. The main focus of the manual is on mechanized harvesting operations in typical conditions found in terra firme forests of the Peruvian Amazon. The themes covered are safety guidelines and equipment, stock survey of commercial timber, directional felling, planning and construction of harvesting infrastructure, skidding and yarding operations